2021
DOI: 10.12688/f1000research.55140.1
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model for the cultivation of polymicrobial biofilms under continuous-flow conditions

Abstract: The airways of people with cystic fibrosis (CF) are often chronically colonised with a diverse array of bacterial and fungal species. However, little is known about the relative partitioning of species between the planktonic and biofilm modes of growth in the airways. Existing in vivo and in vitro models of CF airway infection are ill-suited for the long-term recapitulation of mixed microbial communities. Here we describe a simple, in vitro continuous-flow model for the cultivation of polymicrobial biofilms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Antimicrobial resistance is known to be increased (compared with the planktonic mode of growth) [ 40 ] in biofilms. However, we have recently demonstrated that the continuous-flow setup can be used to cultivate polymicrobial biofilms [ 19 ] and current efforts are aimed at examining how antibiotic challenge affects the population dynamics in this growth mode too. We are also expanding the species repertoire in the system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial resistance is known to be increased (compared with the planktonic mode of growth) [ 40 ] in biofilms. However, we have recently demonstrated that the continuous-flow setup can be used to cultivate polymicrobial biofilms [ 19 ] and current efforts are aimed at examining how antibiotic challenge affects the population dynamics in this growth mode too. We are also expanding the species repertoire in the system.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial/fungal strains used in this study were: P. aeruginosa PAO1 (PA; strain MPAO1 from Colin Manoil), S. aureus ATCC 25923 (SA), and C. albicans SC314 (CA). Artificial sputum medium (ASM) was freshly prepared for every experiment as described in [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Brien et al outlines a model derived from the porcine lung model that uses a continuous flow of media, allowing establishment of steady-state polymicrobial biofilms and planktonic cultures (Fig. 3) [55]. Cubes of agar or porcine bronchiole inoculated with bacteria are suspended in a beaker with continuous ASM inflow and waste outflow.…”
Section: Continuous Flow Polymicrobial Biofilm Modelmentioning
confidence: 99%
“…A continuous flow model of polymicrobial infection [55]. Artificial sputum medium (ASM) is pumped into a culture vessel containing 5cm 3 cubes of agar or ex vivo porcine lung, which serve as a solid substratum for bacteria to grow.…”
Section: Challenges In Antimicrobial Developmentmentioning
confidence: 99%